Unity in diversity : mysticism, messianism and the construction of religious authority in Islam - Mir-Kasimov, Orkhan (Islamic history and civilization ;, 2014)
The edited volume Unity in Diversity: Mysticism, Messianism and the Construction of Religious Authority in Islam explores the role of mystical and messianic groups and movements in the construction and re-construction of religious authority in Muslim societies.